Evolution of Attention During A Teaching Lesson of “Anatomy” in Physical Education Degree’ Students: The Time of Day Effect - H'mida, Cyrine; H'mida, Sabrine; Chtourou, Hamdi (International Journal of Sport Studies for Health, 2019)
The aim of the present study was to examine the evolution of the attention during a lesson of teaching anatomy of the humerus in physical education degree’ students (PES). Sixty-one students (32 males and 29 females), registered in the 1st year PES in the High Institute of Sport and Physical Education of Sfax (University of Sfax, Tunisia) voluntarily participated in the present study. They performed the digit cancellation test at the beginning and at the end of a 90 min teaching session of anatomy at two time-of-day: between 08h00 and 09h30 and between 15h30 and 17h00. The results showed that there is no difference between the males and females groups for the attention (P > 0.05). However, the present study showed that the attention decreased at the end compared to the beginning of the teaching session (P < 0.05). Also, the attention was significantly better in the morning compared to the afternoon hours (P < 0.05). For PES, anatomy requires good attention capacities and the scheduling of these lessons in the morning is better than the afternoon hours.